Core Competencies and Career Insights of CIIP Certification. - Stewart, Kori L. (Radiologic Technology)
This article focuses on the Certified Imaging Informatics Professional (CIIP) certification, established by the American Board of Imaging Informatics (ABII) to standardize expertise in the use and exchange of medical images within complex healthcare systems. The CIIP credential, developed in collaboration with the American Registry of Radiologic Technologists and the Society for Imaging Informatics in Medicine, validates knowledge across clinical, technical, and business domains essential to imaging informatics. The certification exam covers ten key domains, including clinical engineering, image management, and project management, and requires candidates to meet a seven-point qualification system based on experience, education, and continuing education. Studies cited in the article highlight that CIIP certification enhances professional credibility, career advancement, and leadership opportunities, while contributing positively to healthcare quality and technology management.